1973
DOI: 10.1063/1.3253124
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Coexistence Curve Data for Several Binary Liquid Mixtures Near Their Critical Points

Abstract: Experimental data on the coexistence curves for nine binary liquid systems, which meet strict criteria of precision, purity of components, and experimental method, are analyzed in the neighb~rhood of the critical point. The data are examined in terms of a general equation of state which is nonanalytic at the critical point. The results of the computer analysis using weighted non-linear least squares procedures present evidence that some symmetry features of classical equations of state remain; and within the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…Preliminary data [28] at a 2 % accuracy show the existence of a strong negative volume excess in the vicinity of the miscibility gap. These data significantly straighten up the tilt of the rectilinear diameter and give the best agreement between the f3 value obtained from equations (17) and 18and what is expected from the scaling laws [27], considering what hasBbeen obtained already for y and v, i.e. f3 = 0.30 ± 0.05.…”
Section: The Critical Exponents and Parameters -supporting
confidence: 83%
“…Preliminary data [28] at a 2 % accuracy show the existence of a strong negative volume excess in the vicinity of the miscibility gap. These data significantly straighten up the tilt of the rectilinear diameter and give the best agreement between the f3 value obtained from equations (17) and 18and what is expected from the scaling laws [27], considering what hasBbeen obtained already for y and v, i.e. f3 = 0.30 ± 0.05.…”
Section: The Critical Exponents and Parameters -supporting
confidence: 83%
“…(T-Tc)/Tc], and find A = 1.9110.03. Stein and Allen (1973) have fit the bulk lutidine +water coexistence• curve data of ' Loven and Rice (1963) and found A* = 1.95 i 0.70. Thus our value t for A* and hence A3 appears to be reasonable.…”
Section: Coexistence Curvesmentioning
confidence: 92%
“…proportional to 80. We take 80 as the order parameter of the system (Stein and Allen, 1973) and so its behavior is governed by the coexistence curve scaling form…”
Section: Chapter IVmentioning
confidence: 99%
“…It has often been suggested that volume fractions, rather than mole fractions should be used because coexistence curves for binary mixtures are then more nearly symmetric. Unfortunately, this choice of variables does not necessarily guarantee that the true (1 -a) = 0.88 will be observed; for the system 3-methyl pentane/nitroethane, for example, Stein and Allen (1973) obtained (1 -a) = 0.62 from the precise measurements of Wims et al (1969), using volume fractions. In this regard, complete agreement between theory and experiment has not been achieved.…”
Section: Aiche Journalmentioning
confidence: 98%